Differences in induced volatile emissions among rice varieties result in differential attraction and parasitism of Nilaparvata lugens eggs by the parasitoid Anagrus nilaparvatae in the field - Lou, Yonggen; Hua, Xiaoyan; Turlings, Ted; Cheng, Jiaan; Chen, Xuexin; Ye, Gongyin (My University, 2006)
We compared the volatiles of JA-treated plants of six rice varieties and then determined, in the laboratory and field, if they differed in attractiveness to Anagrus nilaparavate Pand et Wang, an egg parasitoid of rice planthoppers. Analyses of volatiles revealed significant differences among varieties, both in total quantity and quality of the blends emitted. On the basis of these differences, the six varieties could be roughly divided into three groups. In a Y-tube olfactometer, female wasps preferred odors from two groups. These preferences corresponded to observed parasitism rates in a field experiment. A comparison of the volatiles with results from behavioral assays and field experiments indicates that the quality (composition) of the blends is more important for attraction than the total amount emitted. The results imply that the foraging success of natural enemies of pests can be enhanced by breeding for crop varieties that release specific volatiles.
Keywords: rice; Anagrus nilaparavate; Nilaparvata lugens; induced plant; volatiles; jasmonic acid; volatiles variability; host-searching; behavior; parasitism; parasitoid; NATURAL ENEMIES; PLANT VOLATILES; ORAL SECRETIONS; JASMONIC ACID; SEMIOCHEMICALS; DELPHACIDAE; HERBIVORES; PREDATORS; HOMOPTERA; SEEDLINGS